The long pentraxin PTX3: a paradigm for humoral pattern recognition molecules. (25th March 2013) - Mantovani, Alberto; Valentino, Sonia; Gentile, Stefania; Inforzato, Antonio; Bottazzi, Barbara; Garlanda, Cecilia
Abstract : Pattern recognition molecules (PRMs) are components of the humoral arm of innate immunity; they recognize pathogen‐associated molecular patterns (PAMP) and are functional ancestors of antibodies, promoting complement activation, opsonization, and agglutination. In addition, several PRMs have a regulatory function on inflammation. Pentraxins are a family of evolutionarily conserved PRMs characterized by a cyclic multimeric structure. On the basis of structure, pentraxins have been operationally divided into short and long families. C‐reactive protein (CRP) and serum amyloid P component are prototypes of the short pentraxin family, while pentraxin 3 (PTX3) is a prototype of the long pentraxins. PTX3 is produced by somatic and immune cells in response to proinflammatory stimuli and Toll‐like receptor engagement, and it interacts with several ligands and exerts multifunctional properties. Unlike CRP, PTX3 gene organization and regulation have been conserved in evolution, thus allowing its pathophysiological roles to be evaluated in genetically modified animals. Here we will briefly review the general properties of CRP and PTX3 as prototypes of short and long pentraxins, respectively, emphasizing in particular the functional role of PTX3 as a prototypic PRM with antibody‐like properties.